Narodowosocjalistyczne prawo w poglądach Szymona Rundsteina - Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The author presents the views of Szymon Rundstein, one of the most eminent European legal scholars and one of the most versatile Polish lawyers of the 20th century, on the law of the total states, in particular of the Third Reich. Rundstein represented phenomenological version of normativism which was chiefly connected to the theories of H. Kelsen, A. Reinach and F. Kaufmann. In his last book titled In Search of Civil Law he significantly modified his previously held theoreticaland-legal opinions and formulated, on the background of the penetrating critique of legal systems of total states which he perceived differently than it is done today by theories of totalitarianism, authoritarianism and Fascism, an original variant of the concept of the relative autonomy of law and of the immutability of the idea of law, the rejection of which must lead to chaos and ultimately to lawlessness. Rundstein attached the biggest importance to the civil law of the Third Reich and of other total states. His resolutely critical assessment revealed a certain characteristic vacillation with respect to the predictions concerning the future fate of law. On the one hand, he maintained that the relentless synchronization of communal existence, the reification of economic life, which constitute the antithesis of personality and individuality of mutual interactions in a large measure made the return to the classical rules of civil law a mere fiction. The occurring changes could, in his opinion, not only lead to the destruction of the concept of private sphere but even to the annihilation of the very idea of law. However, on the other hand, he wanted to believe in a regulatory impact of the idea of law; that is why he observed that his gloomy prophecies about the coming age of darkness either may or may not be fulfilled. The author also presents the analysis of the National Socialist doctrine of the law of nations, made by Rundstein in 1935 which — as the author proves — was original and at least partially brilliant. After the outbreak of World War II Rundstein, though a descendant of the Jewish family, remained in Poland due to patriotic reasons and refused to accept an earlier Hitlerite offer to lecture in English and Swiss universities. For this decision, he paid the ultimate price. Imprisoned in the Warsaw Ghetto, he was subsequently deported in the August of 1942, together with his wife, daughter who was a medical doctor and granddaughter, to the extermination camp in Treblinka where he was murdered, with his family, in a gas chamber.
Keywords: Rundstein, Szymon; totalitaryzm; faszyzm; autorytaryzm; krytyka